2002
DOI: 10.1890/0012-9658(2002)083[2664:hpbfpf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

How Plants Benefit From Providing Food to Predators Even When It Is Also Edible to Herbivores

Abstract: It is well established that plants provide alternative foods to predators of herbivorous arthropods. This provision may facilitate protection against herbivory. However, plants often cannot prevent other organisms from utilizing these foods as well. There are many examples of herbivorous arthropods that can feed on plant‐provided foods such as extrafloral nectar and pollen. The question therefore arises whether individual plants still gain protection when not only the predators, but also the herbivores, can fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 233 publications
(180 citation statements)
references
References 49 publications
4
161
0
15
Order By: Relevance
“…Similar effects might also be achieved by adding a non-pest alternative food source, such as pollen. Several studies have shown the benefit of pollen in terms of enhancing pest control (Nomikou et al 2002(Nomikou et al , 2009van Rijn et al 2002), but so far, this has not resulted in large-scale applications. Our results furthermore suggest that it might be advantageous to allow or create some pest species diversity in a crop, rather than to try to exterminate all phytophages present.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects might also be achieved by adding a non-pest alternative food source, such as pollen. Several studies have shown the benefit of pollen in terms of enhancing pest control (Nomikou et al 2002(Nomikou et al , 2009van Rijn et al 2002), but so far, this has not resulted in large-scale applications. Our results furthermore suggest that it might be advantageous to allow or create some pest species diversity in a crop, rather than to try to exterminate all phytophages present.…”
Section: Discussionmentioning
confidence: 99%
“…Apple pollen was the most suitable alternative food, and supplementing A. swirskii with it resulted in better control of western flower thrips on chrysanthemum (Delisle et al 2015b). Similarly, Leman and Messelink (2015) test various types of alternative food for A. swirskii and Amblydromalus limonicus, but they specifically consider the possibility that western flower thrips also benefits from this food (van Rijn et al 2002). In short-term laboratory experiments, they show that predation of thrips by individual A. swirskii was reduced when pollen was present.…”
Section: This Issuementioning
confidence: 99%
“…A relevant question therefore is how to avoid that predators preferentially feed on the supplied food, resulting in temporary increases of pest populations. In our opinion, supplementing predators such as A. swirskii with superior alternative food is a viable biological control practice, as several studies have shown (van Rijn et al 2002;Nomikou et al 2010;Delisle et al 2015b;Leman and Messelink 2015). Especially when predators and alternative food are introduced into the crop before pests occur, the densities of the predators will, after some Exp Appl Acarol (2015) 65:413-418 415 time, be limited by the availability of the alternative food.…”
Section: Prospectsmentioning
confidence: 99%
See 2 more Smart Citations